Attempts to Unravel and to Overcome The Educational Issues of Nahwu (A Multi-Site Descriptive Study at UINSI Samarinda and UNSIQ Wonosobo) - Ahmad Fadhel Syakir Hidayat; Rifqi Aulia Rahman; Bakri Mohammad Bkheet Ahmed; Wildana Wargadinata (Diwan Media Pustaka, 2024)
Nahwu is an integral part of the curriculum in teaching Arabic in all Islamic educational institutions in the world, either in the form of a separate subject or part of the study of the Arabic language. But when studying it, he found some problems, whether linguistic or non-linguistic, that needed ways to be overcome. Therefore, this research aims to describe and analyze the problems related to teaching science and their solutions. This research is a qualitative research and descriptive multiplicity of sites in Sultan Aji Muhammad Idris Islamic State University Samarinda and the Central Java Quranic Sciences University in Wonosobo in the Department of Arabic Language Teaching, and the research sample of intermediate students in the proficiency of the Arabic language sitting in the fourth level in the subject about 2 and the subject towards developmental. The sources of data in this research are interviews, observation, and documentation, and the data is analyzed using the data analysis method of Miles and Huberman. The results of the research indicate that there are linguistic and non-linguistic problems, and the problems revolve around vocabulary, lack of exercise, short lecture hours, lack of motivation and awareness, lack of diversity of strategies, educational facilities, and students' academic backgrounds. Solutions to these problems are: creating educational programs to memorize vocabulary; improving communication; reviewing the curriculum; directing efforts towards enhancing motivation and awareness; adopting cooperative learning strategies; providing materials using the concept of mind maps or tables; staying on key points identified; providing additional lessons; and improving classroom facilities.